catena-Poly[[bis(N-ethylethylenediamine-κ(2) N,N′)copper(II)]-μ-cyanido-κ(2) N:C-[dicyanido-κ(2) C-palladium(II)]-μ-cyanido-κ(2) C:N] - Akitsu, Takashiro (International Union of Crystallography, 2009)
The title compound, [CuPd(CN)(4)(C(4)H(12)N(2))(2)](n), consists of one-dimensional chains. The Cu and Pd atoms are both located on centers of symmetry in an alternating array of [Cu(N-Eten)(2)](2+) (N-Eten = N-ethylethylenediamine) and [Pd(CN)(4)](2−) units. The Pd—C distances of 1.991 (3) and 1.992 (3) Å are intermediate values compared with the analogous Ni(II) and Pt(II) complexes [Akitsu & Einaga (2007 ▶). Inorg. Chim. Acta, 360, 497–505]. Due to Jahn–Teller effects, the axial Cu—N bond distance of 2.548 (2) Å is noticeably longer than the equatorial distances [Cu—NH(2) = 2.007 (2) and Cu—NHC(2)H(5) = 2.050 (2) Å]. There are interchain hybrogen bonds, with N(—H)⋯N = 3.099(4) Å.